2019
DOI: 10.1111/jpc.14706
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric clinicians' experiences of parental online health information seeking: A qualitative study

Abstract: Aim: The aim of this research was to explore clinicians' experiences of parents' online health information seeking (OHIS) behaviour about selective dorsal rhizotomy for the management of cerebral palsy. Methods: Using qualitative methodology, clinicians likely to have had experience with parents requesting selective dorsal rhizotomy were invited to participate in semi-structured interviews. Interviews with 13 clinicians were recorded, transcribed and inductive content analysis was used to identify, code and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 29 publications
(49 reference statements)
1
19
0
Order By: Relevance
“…This study highlights the ways in which the doctor-parent relationship is evolving through paediatricians' communication approaches with Internet-informed parents, such as improved balance in the doctor-parent relationship. 4,10 The paediatricians' expectations that most parents search online are consistent with recent findings in a paediatric tertiary hospital that almost 90% of parents searched online. [5][6][7]16 Paediatricians were concerned about parents' digital health literacy, in line with recent findings highlighting that parents focus more on relevancy (e.g.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This study highlights the ways in which the doctor-parent relationship is evolving through paediatricians' communication approaches with Internet-informed parents, such as improved balance in the doctor-parent relationship. 4,10 The paediatricians' expectations that most parents search online are consistent with recent findings in a paediatric tertiary hospital that almost 90% of parents searched online. [5][6][7]16 Paediatricians were concerned about parents' digital health literacy, in line with recent findings highlighting that parents focus more on relevancy (e.g.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, the paediatricians in this study most commonly reported using a patient‐centred communication approach when discussing online health information with parents. This study highlights the ways in which the doctor–parent relationship is evolving through paediatricians' communication approaches with Internet‐informed parents, such as improved balance in the doctor–parent relationship 4,10 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A study of 40 parents of children with acute lymphoblastic leukemia (ALL) found that parents turn to SM to meet information needs because the information is immediate, targeted to their specific questions and concerns, and tailored to their roles as parents or caregivers 7 . One study that explored clinicians’ experiences with parents seeking health information online found that clinicians felt obliged to reallocate time in order to help parents better understand the concept of “evidence” in medicine and to respond to perceived critiques of their practices 15 . Parents, furthermore, inevitably encounter conflicting information, testing their trust in their physicians’ advice 15 .…”
Section: Introductionmentioning
confidence: 99%
“…One study that explored clinicians’ experiences with parents seeking health information online found that clinicians felt obliged to reallocate time in order to help parents better understand the concept of “evidence” in medicine and to respond to perceived critiques of their practices 15 . Parents, furthermore, inevitably encounter conflicting information, testing their trust in their physicians’ advice 15 . Yet these challenges—navigating discordant information and building trust in this age of SM and disinformation—have received scant attention in the literature.…”
Section: Introductionmentioning
confidence: 99%